1998
DOI: 10.1046/j.1365-2648.1998.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Guided participation and development of care‐giving competencies for families of low birth‐weight infants

Abstract: The concept of guided participation is central to theory for supporting families in developing competencies for care of their low birth-weight infants. Guided participation is a process through which an experienced person helps another person who has less experience to become competent in practices that are personally and socially meaningful practices of everyday life. A practice is made up of socially formed activities directed to accomplishing a recurring goal. For a parent, infant care-giving encompasses pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 25 publications
(37 reference statements)
1
70
0
1
Order By: Relevance
“…Hopefully, such interventions can facilitate improved outcomes in a range of areas, including child development and family functioning and future research into such outcomes is encouraged. 46 Limitations One limiting factor in this investigation is the reliance on retrospective reporting. Biases in memory or reporting may have impacted the present findings.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Hopefully, such interventions can facilitate improved outcomes in a range of areas, including child development and family functioning and future research into such outcomes is encouraged. 46 Limitations One limiting factor in this investigation is the reliance on retrospective reporting. Biases in memory or reporting may have impacted the present findings.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…15 Guided participation can be applied to the feeding process and used to shape a mothers' working model of feeding. 16 In guided participation, an experienced or more expert person helps another person with less experience to become competent in activities that are meaningful in everyday life.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…A cursory review of the literature finds many interventions shown to improve parental coping, knowledge and parenting skills and to reduce stress. [34][35][36] Although many of these interventions are time-and labor-intensive, even less-intensive measures, especially when begun early, may be effective. 36 Many authors and the AAP call for increased social support for these families.…”
Section: Discussionmentioning
confidence: 99%